Digitalization’s Effect on the Sectoral Structure Change in the Economy: a Comparative Analysis of Ukraine and Selected Countries - Pizhuk, Olha; Lazebnyk, Larysa; Mamonova, Hanna (Comparative Economic Research. Central and Eastern Europe, 2022)
This article examines the impact of digital transformation on changes in the sectoral structure of Ukraine’s economy, other post‑communist countries, and countries with highly developed economies. Firstly, we estimate the structural changes and differences in the sectoral model by gross value‑added and sectoral employment model by country using Ryabtsev’s index. Secondly, we calculated the forecast of changes in the researched economies' sectoral structures for 2021 and 2025 using discrete Markov processes. The forecasts made it possible to determine the direction of socio‑economic progress of highly developed and post‑communist countries. Thirdly, assuming that the development of ICT technologies caused the sectoral changes identified as a result of the assessment, we analyzed available level ratings of the digital transformation of the selected economies and named global trends in ICT. Finally, we determined the impact of the ICT index on the substantiality of sectoral changes in the economies of post‑communist countries and countries with highly developed economies. The study results allowed us to conclude that digital technology development affects the economy’s structural changes indirectly due to the reallocation of labor resources from one sector to another. The article substantiates the need to improve the economy’s sectoral model by adding industries related exclusively to the digital economy.